(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
As a result of the reforms implemented in our country, great practical works are being expressed in various aspects of the economy - art, agriculture, transport, tourism, as well as social spheres - health care, sports, education system. At the same time, a number of good actions aimed at improving the spiritual environment and cultural life in our country are an example of high attention to our historical values and ancestors.